Inclusion in the top 2% of the top researchers in the scientific field "Information & Communication Technologies" (subfieldof: "Artificial Intelligence & Image Processing"). Data for updated science-wide author databases of standardized citation indicators - Lanitis, Andreas (My University, 2026)
https://topresearcherslist.com/Home/Profile/1120493
Keywords: Worlds Top Scientists